DESIGN, FABRICATION AND EXPERIMENTAL STUDY OF A FLAT PLATE COLLECTOR SIMULATOR - Rodríguez O. R. S.; Koury, R. N. N.; Maia, A. A. T. (Revista de Engenharia Térmica, 2016)
In this article, a flat plate collector simulator was designed and developed based on the use of electric heaters and a power control system. A computational algorithm aimed at determining the relationship between the incident solar energy on the collector absorber plate and the corresponding amount of power that must be supplied by the electrical resistance was developed. The variation in power is obtained by regulating the voltage fed through the assembly. With such regulation, simulating typical profiles of insolation over a day was possible. In the assessment of the average solar radiation data obtained by satellite imagery analysis (SWERA Project), the results showed that the thermal behavior of the simulator collector was close with a real behavior. Therefore, it can be used to determine the operating characteristics of auxiliary power systems as heat pumps, electrical systems or water heating systems. Different thermodynamic processes to determine the main losses of a collector evaluated the simulation parameters.